Comportamento intuitivo no preparo de equipes cirúrgicas e a percepção da equipe: o caso de um hospital privado em São Luís, Maranhão - PINTO, Raissa Muniz (2019)
Intuitive behavior in preparing surgical teams can prevent hospital infections. Thus one can consider the prevention of infections strongly based on the task of hand hygiene; and also that the notion of error can be related to the product and not to the user. Thus, this study seeks to verify the relationship between the legal and normative prescription of surgical teams preparation, and the perception of this team when performing the tasks, in order to highlight possible contributions to the development of intuitive presurgical artifacts and environments aiming at safety, health, comfort and efficiency of the team and consequently of the patients, through a case study in a private hospital sector in São Luís, Maranhão. Observations were conducted, followed by the elaboration of a functional action flowchart, application of questionnaires and physical survey of the hospital environment. It was possible to identify points of disagreement between the norm, the literature and the performed, in the physical environment, artifacts and procedures, as well as highlighting artifacts that deserve further research to improve hospital safety, such as gloves, masks and surgical overalls.